Environmental Impact of Domestic Waste on Soil and Water Quality in St. Thomas Parish, Jamaica - Candace Cuthbert; Derwin Ramón Calatayud Márquez (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to analyze the impact of domestic waste on environmental conditions in St. Thomas Parish, Jamaica, from environmental and public health perspectives. Methodology: A mixed-methods approach with a cross-sectional design was employed, combining environmental sampling (soil and water analysis) and field observations with community-based insights. Data were collected from multiple sampling sites representing coastal, residential, and semi-urban areas and analyzed using descriptive statistical and qualitative techniques. Main Findings: The findings revealed that domestic waste is dominated by organic (46–55%) and plastic (30–39%) components, with daily waste volumes reaching up to 35 kg per site. Soil quality showed acidic conditions (pH 5.6–6.2) with moderate to high contamination, while water quality was characterized by elevated turbidity (18–25 NTU) and microbial presence. Environmental assessments indicated degraded to severely degraded conditions, which were supported by community reports of inadequate waste management practices, such as open dumping and burning. Novelty/Originality of this study: This study provides a localized, integrative analysis linking environmental degradation with community waste practices in a less-explored parish-level setting, offering new insights into the intersection of environmental science and public health.